Me and My Avatar: Exploring Users' Comfort with Avatars for Workplace Communication - Inkpen, Kori; Sedlins, Mara (CSCW 2011, 2011)
This paper describes results from a large-scale survey to explore users’ comfort with different styles of avatars for workplace communication. Thirty-one avatars were evaluated based on users’ ratings along several dimensions and grouped into five different clusters. The highest rated cluster was the set of formal, realistic avatars that users did not feel were creepy. These avatars were ranked comparatively with webcam photos, and users felt that they would be appropriate for work. Our results also revealed that realism is nuanced, as avatars in another cluster were also rated high on realism, but were felt to be inappropriate for work. Finally, this work also demonstrates that people are more particular concerning which type of avatar they are represented by, compared to ones they interact with.